2017
DOI: 10.1038/s41598-017-01706-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkaline microwaving pretreatment on anaerobic digestion and biogas production of swine manure

Abstract: Microwave assisted with alkaline (MW-A) condition was applied in the pretreatment of swine manure, and the effect of the pretreatment on anaerobic treatment and biogas production was evaluated in this study. The two main microwaving (MW) parameters, microwaving power and reaction time, were optimized for the pretreatment. Response surface methodology (RSM) was used to investigate the effect of alkaline microwaving process for manure pretreatment at various values of pH and energy input. Results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Hydrolysis, fermentation, acetogenesis, and methanogenesis mainly consist of the whole process from macromolecular organic substances to methane production [1]. In the progress of fermentation, which may also be artificially intervened, acidogenic fermentation bacteria convert soluble monomers into terminal products, such as volatile fatty acid [2,3]. The formation of methane has traditionally been identified as a result of methanogen metabolism in the final step of organic matter fermentation in anaerobic terrestrial environments and artificial digestion [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrolysis, fermentation, acetogenesis, and methanogenesis mainly consist of the whole process from macromolecular organic substances to methane production [1]. In the progress of fermentation, which may also be artificially intervened, acidogenic fermentation bacteria convert soluble monomers into terminal products, such as volatile fatty acid [2,3]. The formation of methane has traditionally been identified as a result of methanogen metabolism in the final step of organic matter fermentation in anaerobic terrestrial environments and artificial digestion [4].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that addition of ultrasonication during AD was more effective as compared to the pretreatment stage. Tao Yu et al 15 also reported similar increments in the biogas production when applied microwave pretreatment on swine manure. Moreover, comparison between ultrasonic treatment during both stages (KOH U -AD U ) with KOH U showed no signicant difference in biogas yield.…”
Section: Effect On Physical Morphologymentioning
confidence: 75%
“…12 Addition of co-pretreatment with alkali such as steam explosion, microwave, irradiation, adsorption and ultrasonication are reported for improving the disruption of lignin content. [13][14][15] Yang et al 16 applied irradiation pretreatment on wheat straw using g radiation to determine the effects and aer effects of pretreatment and suggested effective breakdown of wheat straw structure. Similarly, Wu et al 17 reported that combination of alkalization and adsorption technique, in two step pretreatment of wheat straw was effective for enhanced hydrolysis during pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Huijgen et al [21] used dilute acid to pretreat WS and found that it could absorb more Cd(II) from aqueous solutions, which may due to the reason that hemicelluloses could be converted into the corresponding monosaccharide by dilute acid pretreatment. Furthermore, using microwave irradiation to pretreat WS is also a common way to achieve high adsorption capacity of Pb(II) and Cd(II) [22,23]. Those pretreatment methods could modify the surface characteristics/groups of the straws, either by removing or masking the groups or by exposing more metal-binding sites [24].…”
Section: Introductionmentioning
confidence: 99%